Analisis Sistem Bagi Hasil Akad Mudharabah dalam Perspektif Ekonomi Islam Pada Bank Syari'ah: Bagi hasil - Ivanka Mira Nur aini (Universitas KH. A. Wahab Hasbullah, 2021)
In an effort to spread Islamic teachings in the millennial era with the existing pattern of development in the economic field based on Islamic sharia and in its development applying a profit sharing system (mudharabah) between the two parties. Although basically humans are given the freedom to conduct transactions (mu’amalah) but in its development it must be on the basis of Islamic law with a fiqh perspective and this is also highly expected so that the mudharabah contract can also be used and can also be used and can also be developed in Islamic Banking. The main capital in this concept is not only money but trust and a high social spirit. Keywords: Profit sharing, mudharabah contract, islamic economics, islamic bank